Effects of parenting classes and economic strengthening for caregivers on the cognition of HIV-exposed infants: a pragmatic cluster randomised controlled trial in rural Zimbabwe - Frances M Cowan; Lorraine Sherr; Victoria Simms; Helen Mebrahtu; Zivai Mupambireyi; Andrea M Rehman; Rudo Chingono; Edward Matsikire; Rickie Malaba; Patience Ndlovu (BMJ Global Health)
Introduction HIV-exposed children show signs of developmental delay. We assessed the impact of a pragmatic multicomponent intervention for caregivers of HIV-exposed children aged 0–2 years in Zimbabwe.Methods We conducted a cluster-randomised trial from 2016 to 2018. Clusters were catchments surrounding clinics, allocated (1:1) to either National HIV guidelines standard of care or standard care plus an 18-session group intervention comprising i) early childhood stimulation (ECS) and parenting training with home visits to reinforce skills and retention in HIV care; ii) economic strengthening. Primary outcomes measured 12 months after baseline (4.5 months postintervention completion) included: i) global child development measured using the Mullen early learning composite score; ii) retention in HIV care. Analysis used mixed effects regression to account for clustering and adjusted minimally for baseline prognostic factors and was by intention to treat.Results Thirty clusters, 15 in each arm, were randomised. 574 dyads were recruited with 89.5% retained at follow-up. Ninety one of 281 (32.4%) were recorded as having received the complete intervention package, with 161/281 (57.3%) attending ≥14 ECS sessions. There was no evidence of an intervention effect on global child development (intervention mean 88.1 vs standard of care mean 87.6; adjusted mean difference=0.06; 95% CI −2.68 to 2.80; p=0.97) or infant retention in care (proportion of children who had missed their most recent HIV test: intervention 21.8% vs standard of care 16.9%, p=0.18). There was weak evidence that the proportion of caregivers with parental stress was reduced in the intervention arm (adjusted OR (aOR)=0.69; 95% CI 0.45 to 1.05; p=0.08) and stronger evidence that parental distress specifically was reduced (intervention arm 17.4% vs standard of care 29.1% scoring above the cut-off; aOR=0.56; 95% CI 0.35 to 0.89; p=0.01).Conclusion This multicomponent intervention had no impact on child development outcomes within 4.5 months of completion, but had an impact on parental distress. Maternal mental health remains a high priority.Trial registration number PACTR201701001387209.